Extracorporeal Shockwave Therapy for Chronic Venous Ulcers: A Randomized Controlled Trial: - Vahdatpour, Babak; Taheri, Parisa; Shahbandari, Morteza; Parvaresh, Mehrnoosh (Galen Medical Journal, 2021)
Background: Chronic venous ulcers (CVUs), demanding specialized care, are still a major socioeconomic problem facing health care systems worldwide. This study’s main goal was evaluating the efficacy of ESWT application as an AT in the treatment of wounds for curing CVUs. Materials and Methods: 50 patients presenting with CVUs were divided into two groups of ESWT and control randomly. Then, ESWT was applied one session per week, during four weeks, along with routine CB. The control group also received sham ESWT together with CB. In this respect, pain score, wound size, patient satisfaction and quality of life (QoL) using the Charing Cross Venous Ulcer Questionnaire (CCVUQ) were consequently assessed at baseline, week four, and week eight and then compared between both groups. Results: The findings showed that patients receiving ESWT along with CB had significantly lower pain and were also feeling more satisfied than the cases undergoing CB alone (P<0.05). The significant efficiency of ESWT in improving the healing process of CVUs was further observed (P<0.05). In addition, QoL, assessed by the CCVUQ, was significantly higher in patients receiving ESWT (P<0.05). Conclusion: These findings established that ESWT was a feasible and safe option to treat patients presenting with CVUs in another word, ESWT seems to be a safe and effective adjunct therapy (AT) compared with CB in patients with CVUs. [GMJ.2021;10:e1931]